2018
DOI: 10.2174/1573399812666161214141716
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Urinary 8-Iso-Prostaglandin F2α and Hydrogen Peroxide Toward Renal Function in T2DM Patients Consuming Sulfonylurea and Combination of Metformin-Sulfonylurea

Abstract: The two treatments did not have any significant differences in antioxidant activity. However, an increase of urinary 8-iso-prostaglandin F2. and hydrogen peroxide which correlates with eGFR in the total sample may play a significant role in the pathophysiology of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This is consistent with our observation that the associations were stronger when we considered baseline oxidant stress in relation to longitudinal outcomes compared with the analysis of longitudinal oxidant stress measures with longitudinal outcomes. Cross-sectional studies that have measured urinary F 2 -isoprostanes have reported positive associations with eGFR [46][47][48] , and one also found a negative association with albuminuria. Our results provide evidence of this same phenomenon even in a longitudinal setting, and is supported by our consistent observation that urinary oxidant stress biomarkers were associated with a reduced hazard of RRT.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our observation that the associations were stronger when we considered baseline oxidant stress in relation to longitudinal outcomes compared with the analysis of longitudinal oxidant stress measures with longitudinal outcomes. Cross-sectional studies that have measured urinary F 2 -isoprostanes have reported positive associations with eGFR [46][47][48] , and one also found a negative association with albuminuria. Our results provide evidence of this same phenomenon even in a longitudinal setting, and is supported by our consistent observation that urinary oxidant stress biomarkers were associated with a reduced hazard of RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Small lipids in the form of eicosanoids have the capacity to be either proinflammatory or anti‐inflammatory and pro‐resolution (Dennis & Norris ) and have been linked to peroxidation of membrane lipids (Sauriasari et al. ; Van't Erve et al. ).…”
Section: Future Studies and Challengesmentioning
confidence: 99%
“…More studies should be conducted on mediators of oxidative stress such as lipids. Small lipids in the form of eicosanoids have the capacity to be either proinflammatory or anti-inflammatory and pro-resolution (Dennis & Norris 2015) and have been linked to peroxidation of membrane lipids (Sauriasari et al 2016;Van't Erve et al 2016). For example, in dry eye, the small lipid prostaglandin E2 (PGE2) has been found to increase and prostaglandin D2 (PGD2) to decrease in the tears (Shim et al 2012).…”
Section: Future Studies and Challengesmentioning
confidence: 99%
“…This result was in line with the study that has been conducted previously, in which the level of urinary 8-iso-Prostaglandin F2α in metformin-sulfonylurea group was lower than sulfonylurea group. 11 It is known that metformin produced significant effect on the malondialdehyde, a lipid peroxidation product, whereas sulfonylurea was not. 12 Thus, metformin could be more effective in reducing the oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Glomerular filtration rate is known to have a positive correlation with levels of 8-iso-Prostaglandin F2α. 6,11 The linear regression analysis results in albuminuric subjects (n=55) indicate HbA1c and the use of a combination of metformin-sulfonylurea were the most predictive factors for increased UACR, after controlled by age, gender, IMT, systolic blood pressure, 8-iso-Prostaglandin F2α, smoking habit and exercise habit (Table 4). It is reported that the use of sulfonylureas compared with metformin for initial treatment of diabetes were associated with an increased hazard of cardiovascular disease events or death, through UACR as one of the markers.…”
Section: Bivariate Correlationmentioning
confidence: 99%